Applied Technological Direction of Power Plant Ash and Slag Waste Management when Kuznetsk Bituminous Coal is Burned; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Lihach S. A. Snejana; Grishchernko M. V. Maria; Kulesh R. N. Roman Nikolaevich; Lebedev V. M. Vitali; Orlova K. Yu. Kseniya Yurievna (2016, 2016)
Title screen